2003
DOI: 10.1002/bies.10366
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐cancer selection as a source of developmental and evolutionary constraints

Abstract: Recently at least two papers have appeared that look at cancer from an evolutionary perspective. That cancer has a negative effect on fitness needs no argument. However, cancer origination is not an isolated process, but the potential for it is linked in diverse ways to other genetically determined developmental events, complicating the way selection acts on it, and through it on the evolution of development. The two papers take a totally different line. Kavanagh argues that anti-cancer selection has led to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 31 publications
0
66
0
Order By: Relevance
“…Putative limits on disparity may either be intrinsic (e.g. developmental [48,193]) or extrinsic (e.g. ecological [27,204,205]), but both imply constraints on available morphospace that might be reflected in the rate of evolution of novel morphology throughout the lifetime of a clade.…”
Section: Resultsmentioning
confidence: 99%
“…Putative limits on disparity may either be intrinsic (e.g. developmental [48,193]) or extrinsic (e.g. ecological [27,204,205]), but both imply constraints on available morphospace that might be reflected in the rate of evolution of novel morphology throughout the lifetime of a clade.…”
Section: Resultsmentioning
confidence: 99%
“…similar links to cancer for variation in number of ribs in humans and mice [66], suggest that anticancer selection strongly selects against morphogenetic variants and leads to evolutionary conservatism in morphology [40,66]. Such selection is mediated by balances between cell proliferation and differentiation [43]; indeed, many genes involved in embryogenesis are also proto-oncogenes (genes that can mutate to oncogenes) or tumor suppressor genes (some of which control the extensive apoptosis that characterizes normal development), and cancer commonly involves cellular dedifferentiation to a more or less embryonic state [5].…”
Section: Reviewmentioning
confidence: 96%
“…Evolution of genes and genetic systems promoting cancer Recent studies have shown how genes promoting cancer can spread via the pleiotropic effects of strong selection in other contexts [40,41]. Thus, pediatric cancers are rare, apparently as a result of their strongly negative fitness effects, but they are concentrated in two tissues, brain and bone, that have undergone striking recent evolutionary increases in size and growth trajectories along the human lineage.…”
Section: Evolution Of Cancer Risk and Anticancer Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, an incidence higher than 1% has only been found in hospitals or isolated populations (Galis et al 2006). An incidence higher than 25% hase only been found in children with leukemia, brain tumours and neuroblastoma (Schumacher et al 1992;Galis & Metz 2003;Merks et al 2005) and in deceased fetuses and infants (Galis et al 2006;Furtado et al 2011;ten Broek et al 2012). Along with the high incidence of cervical ribs in mammoths, the size of the articulation facets is particularly large (Figs.…”
Section: Discussionmentioning
confidence: 99%